Problems Resulting from Filing an Effort for Judicial Review of the Cancellation of a Bankruptcy Decision which was preceded by an Application for Postponement of Debt Payment Obligations (Analysis of Supreme Court Decision No. 96 PK/PDT.SUS-PAILIT/2014) - Lase, Intan Nurjannah; Sunarmi, Sunarmi; Ginting, Budiman; Harianto, Dedi (Formosa Journal of Applied Sciences, 2023)
The method used in writing this thesis is a normative juridical research method. The nature of this research is prescriptive, using data collection techniques, namely library research and interview guides to complete secondary data. The results of the research found that legal certainty regarding the cancellation of a bankruptcy decision which was preceded by a PKPU application caused legal uncertainty because it was in conflict with the Bankruptcy Law and SEMA Number 4 of 2014. The Supreme Court's decision gave rise to legal consequences, namely the resolution of the case took longer because it was not certain when the case would end. , cases are piling up at the Supreme Court, with legal action being filed, the costs of the proceedings will become more expensive